Effect of Modification with Various Epoxide Compounds on Mechanical, Thermal, and Coating Properties of Epoxy Resin - Alaaddin Cerit; Mustafa Esen Marti; Ulku Soydal; Suheyla Kocaman; Gulnare Ahmetli (International Journal of Polymer Science)
Epoxy resin (ER) was modified with four different epoxide compounds, 4,5-epoxy-4-methyl-pentane-2-on (EMP), 3-phenyl-1,2-epoxypropane (PhEP), 1-chloro-2,3-epoxy-5-(chloromethyl)-5-hexene (CEH), and a fatty acid glycidyl ester (FAGE), to improve its chemical and physical properties. The effects of the addition and amount of these modifiers on mechanical, thermal, and coating properties were investigated. Atomic force microscopy was used to observe the changes obtained with the modification. The influence of the modifying agents on the curing process was monitored through FTIR spectroscopy. The curing degrees of ER and modified ERs (M-ERs) were found to be over 91%. The results showed that tensile strength of ER improved till 30% (wt.) with addition of the modifier content. Modification with EMP and PhEP remarkably enhanced the thermal stability of ER to be highly resistant to the corrosive media.